Evaluation of the reality of the computer and information technology curriculum for the second intermediate grade in The Kingdom of Saudi Arabia in the light of the constructivist theory - Almuzaini, Sara Homoud; Alshebel, Manal Abdulrahman (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to assess the reality of the computer and information technology curriculum for the second intermediate grade in the Kingdom of Saudi Arabia in the light of the constructivist theory. To achieve the objectives of the study, the researcher used the descriptive survey method, and the study sample consisted of (150) computer teachers for the intermediate stage in Riyadh for the academic year 1443 AH. The study tool consisted of: a questionnaire that consisted of (37) items distributed over five dimensions. The study reached the following results: The averages representing the constructivist educational objectives in the computer and information technology curriculum for the second intermediate grade in the Kingdom of Saudi Arabia ranged between (2.79 and 4.13). The averages representing the content of constructivist learning ranged between (3.47 and 3.89). The averages representing the constructivist educational activities ranged between (3.21 and 3.97). The averages representing the constructivist teaching strategies ranged between (3.37 and 3.99). The averages representing the constructivist evaluation ranged between (3.40 and 4.00). And that the categorical variables: academic qualification, years of teaching experience and number of training courses did not have a statistically significant effect on the perceptions of computer teachers towards the reality of the computer and information technology curriculum for the second intermediate grade in the Kingdom of Saudi Arabia in light of the constructivist theory. In light of the results of the study, the researcher made a number of recommendations, including: Expanding the employment and building dimensions of the computer and information technology curriculum for the second intermediate grade in the Kingdom of Saudi Arabia and all educational curricula in light of the constructivist theory; Which contributes to achieving its positive repercussions on the educational process.